A Qualitative Study of Two Oregon Family Medicine Clinics to Explain Parent and Child Healthcare Initiation and Engagement. (November 2022) - Angier, Heather; Wyte-Lake, Tamar; Williams, Shannon; McCrimmon, Sara; Moreno, Laura; E DeVoe, Jennifer; Cohen, Deborah
Background: Parental factors are associated with children's receipt of recommended care but not adequately described.Methods: We conducted a qualitative study of patients with at least two visits who were a primary caregiver for a child who also had at least two visits at the same clinic in 1/2018–12/2019 from two Oregon family medicine clinics. We stratified patients by child age and number of caregiver visits and randomly selected caregivers. Participants were interviewed in accordance with approval by our Institutional Review Board between 12/2020 and 4/2021. The data were analyzed using a grounded theory approach.Results: 12 caregivers (termed parents) were interviewed; half were single parents and three-quarters had a history of substance use disorder and/or a mental health condition. Parents focused on the importance of keeping themselves healthy to keep their families healthy. They described similar reasons for choosing to initiate and continue care for themselves and their children at the same clinic, including: convenience, trust, relationships, and receiving whole-person and whole-family care. Many valued having a healthcare "home" for their entire family. We developed a figure that highlights three themes that capture the interrelated factors parents identified as supporting healthcare use for themselves and their families. These overarching themes included: healthcare initiation; healthcare engagement and continuity; and parent bringing child to the same clinic for healthcare.Conclusion: Our data suggests that long-standing patient-clinic relationships for parents and children can support family-focused healthcare.